Supply chain strategies for speciality foods: a Norwegian case study. Issue 11 (17th August 2016) - Dreyer, Heidi C.; Strandhagen, Jan O.; Hvolby, Hans-Henrik; Romsdal, Anita; Alfnes, Erlend
Abstract: Despite strong market interest in speciality foods, producers find market access and distribution challenging. This exploratory research includes a literature review and five case studies of supply chains relating to shellfish, cheese, meat, potato and miscellaneous speciality foods in the mid-Norway region. The study identifies key supply chain configuration parameters from the extant literature, and these are used to analyse the cases. The study makes three main contributions to the literature: an analytical framework for analysing the supply chain characteristics of speciality foods; important supply chain factors for accessing the conventional food supply chain; and five propositions for improving market access. We argue that the speciality foods supply chain should be configured according to these propositions to ensure responsiveness to customer needs and to strengthen market access.